The Relationship between Digital Health Literacy and Cyberchondria towards Students of State Senior High School 1 Cirebon City in 2026 - Goeshticha, Aulia Halliza; Subianto, Totok; Elfi; Haryanto, Yanto (LPPM Universitas Dhyana Pura, 2026)
With the advancement of digital technology, the internet has become the primary source of health information, especially for teenager. However, difficulty in evaluating this information can lead to cyberhondria. This study aims to examine the relationship between digital health literacy and cyberchondria towards students at SMAN 1 Cirebon City. This study employs a quantitative correlational cross-sectional approach. The study involved students from SMAN 1 Cirebon City with a sample size of 145 participants using quota sampling. The instruments used were the Electronic Health Literacy Scale Indonesian Version (I-eHEALS) to measure digital health literacy, while the Cyberchondria Severity Scale-12 (CSS-12) was used to measure cyberchondria via a 1–5 Likert scale questionnaire. The was used to analyze the data to determine the relationship between the two variables. Regarding digital health literacy, the highest percentages were found among female students (90.0%) and 10th-grade students (90.0%). Regarding cyberchondria, the highest percentages were found among female students (69.2%) and 10th-grade students (85.7%). According to Spearman’s correlation test, a correlation coefficient of 0.375 falls into the weak category and indicates a significant association between digital health literacy and cyberchondria among students at SMAN 1 Cirebon (p = 0.000 < 0.05). This study serves as a foundation for the development of digital health literacy education that emphasizes information evaluation skills to minimize the risk of cyberchondria.